2019
DOI: 10.1002/ps.5269
|View full text |Cite
|
Sign up to set email alerts
|

Cyantraniliprole seed treatment efficiency against Agrotis ipsilon (Lepidoptera: Noctuidae) and residue concentrations in corn plants and soil

Abstract: BACKGROUND: The black cutworm Agrotis ipsilon is the most destructive early season insect pest of corn. In this study, the control efficiency of cyantraniliprole seed treatment against A. ipsilon was evaluated, and the residual concentrations of cyantraniliprole and its metabolite J9Z38 in the stalks of corn seedlings and soil were investigated. RESULTS:Plant pot experiments showed that A. ipsilon larval mortality was greater than 92% and that the percentage of corn seedlings damaged by A. ipsilon was less tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 29 publications
2
27
0
1
Order By: Relevance
“…Because of the high toxicity of IN-J9Z38, cyantraniliprole and IN-J9Z38 have been included for MRL (maximum residue level) compliance and for estimating dietary intake of processed plant commodities (JMPR, 2015). Field dissipation of cyantraniliprole in watermelon, pak choi, cucumber, tomato, rice, pepper, corn, and proso millet after foliar application has been reported by various researchers (Dong et al, 2012;Hongmei et al, 2014;Hu et al, 2013;Lee et al, 2019;Sun, Feng, Tang, & Qin, 2012;Zhang et al, 2013;Zhang et al, 2019). To the best of our knowledge, dissipation of cyantraniliprole residues in cabbage and soil under subtropical conditions prevailing in India has not been reported in literature.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Because of the high toxicity of IN-J9Z38, cyantraniliprole and IN-J9Z38 have been included for MRL (maximum residue level) compliance and for estimating dietary intake of processed plant commodities (JMPR, 2015). Field dissipation of cyantraniliprole in watermelon, pak choi, cucumber, tomato, rice, pepper, corn, and proso millet after foliar application has been reported by various researchers (Dong et al, 2012;Hongmei et al, 2014;Hu et al, 2013;Lee et al, 2019;Sun, Feng, Tang, & Qin, 2012;Zhang et al, 2013;Zhang et al, 2019). To the best of our knowledge, dissipation of cyantraniliprole residues in cabbage and soil under subtropical conditions prevailing in India has not been reported in literature.…”
mentioning
confidence: 90%
“…The insecticide has shown very high efficacy against fruit and shoot borer in brinjal (Kodandaram, Rai, Sireesha, & Halder, 2015;Sharma, Chandel, & Sharma, 2018); flea beetle and caterpillar in grapes (Yadav, Kamte, & Jadhav, 2013); whitefly, fruit fly, serpentine leaf miner, thrips, red pumpkin beetle, and fruit borer in gherkins (Balikai & Mallapur, 2015) under Indian conditions. Cyantraniliprole is reportedly highly toxic to honeybees and moderately toxic to most aquatic species and earthworms (PPDB, 2018) but has shown residue buildup in soil after repeated applications (Zhang et al, 2019). Field application of cyantraniliprole resulted in the formation of several metabolites, the major one being IN-J9Z38 (NZFSA, 2013), which is more toxic to honeybees than the parent molecule (Anonymous, 2014).…”
mentioning
confidence: 99%
“…Studies have shown that cyantraniliprole seed treatment significantly reduces infestation by the rice water weevil (Lissorhoptrus oryzophilus Kuschel), and rice cultivation treated with cyantraniliprole resulted in fewer larvae and pupae compared to rice treated with other insecticides [30,31]. High mortality of Agrotis ipsilon larvae also occurred when maize plants were treated with cyantraniliprole [12]. Cyantraniliprole is highly toxic to Helicoverpa assulta Guenée, and the LC05, LC15, and LC30 concentration of cyantraniliprole reduced the percentage of pupating larvae and increased the percentage of adults with deformities [32].…”
Section: Discussionmentioning
confidence: 99%
“…Sci. 2022, 12, 1297 2 of 10 effective against a broad spectrum of insect pests, including lepidoptera, dipteran leafminers, aphids, leafhoppers, psyllids, beetles, whiteflies, thrips, and weevils [8,[12][13][14][15][16]. Owing to its structural specificity to insect ryanodine receptors over mammalian counterparts, cyantraniliprole has also been shown to be safe for non-target vertebrates [8,16].…”
Section: Introductionmentioning
confidence: 99%
“…Females allowed to lay their eggs on muslin strips that were fixed on the top of the jars. These strips were transferred into Petri dishes and, after egg-laying, kept in an incubator under constant temperature of 25°C ± 1°C and 70-80 RH% (Zhang et al 2019b), until hatching. The newly hatched larvae were transferred into small glass jars and provided daily with castor leaves as a source of food.…”
Section: Rearing Of Agrotis Ipsilonmentioning
confidence: 99%